A sensitive, simple and rapid HPLCâMS/MS method for simultaneous quantification of buprenorpine and its N-dealkylated metabolite norbuprenorphine in human plasma - Yi-Ya Wang; Xiao-Hang Shen; Hao Li; Feng-Ju Chen; Yan Fu; Li Ding (Elsevier, 2013)
A sensitive, simple and rapid high performance liquid chromatography-tandem mass spectrometry (HPLCâMS/MS) method was developed and fully validated for the simultaneous quantification of buprenorphine (BUP) and its N-dealkylated metabolite norbuprenorphine (NBUP) in 200Î¼L human plasma. Human plasma samples were prepared using liquidâliquid extraction, and then separated on a Shiseido MG C18 (5Î¼m, 2.0mmÃ50mm) via 4.1min gradient elution. Following electrospray ionization, the analytes were quantified on a tripleâquadrupole mass spectrometer in multiple-reaction-monitoring (MRM) positive ion mode. Linearity was achieved from 25.0 to 10000pg/mL for buprenorphine, from 20.0 to 8000pg/mL for norbuprenorphine with r2>0.99. The method was demonstrated with acceptable accuracy, precision and specificity for the detection of buprenorphine and norbuprenorphine. Recovery was 81.8â88.8% for buprenorphine and 77.0â84.6% for norbuprenorphine, and the matrix effect was 95.6â97.4% for buprenorphine and 94.0â96.9% for norbuprenorphine; all were not concentration dependent. With validated matrix and autosampler stability data, this method was successfully applied in a bioequivalence study to support abbreviated new drug application. Keywords: Buprenorphine, Norbuprenorphine, Human plasma, HPLCâMS/MS